(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
The lady bugs Olla roatanensis Vandenberg (Coccinellidae, Coleoptera) and Cheilomenes sexmaculata Fabricius are reported for first time from Ecuador and Peru, both Coleoptera: Coccinellidae have been found on mangrove ecosystems. The morphology and behavior of final larval stage, pupe and adult of Olla roatanensis are described.